Minimization of the total completion time for asynchronous transmission in a packet data - transmission system - Piórkowski, Adam; Werewka, Jan (Zielona Góra: Uniwersytet Zielonogórski)
The minimization of the total completion time for asynchronous transmission in distributed systems is discussed. Attention is focused on the problem of message scheduling on part of the sender. Messages to be sent form a queue, and the order in which they are to be sent has to be first established. The methods of scheduling messages, which minimize the factor of the total completion time, are presented herein. The message-scheduling problem becomes considerably complicated when the stream of data transmitted between the sender and the receiver is organized into packets
Keywords: message scheduling; message queuing; distributed systems; real-time systems